Measuring Relationship Satisfaction: Is it Possible for Black Gay Male Couples to be Satisfied in a Relationship?. Issue 8 (2nd August 2016) - Edwards, Willie J.
ABSTRACT: This study investigated the satisfaction of forty-two Black gay males who acknowledged that they were presently in a same-sex relationship, identifying themselves as a couple. This study challenged some of the myths and stereotypes associated with gay males and their relational experiences. This study used a questionnaire to gather descriptive information about the participants' relationship satisfaction, dyadic adjustment, longevity of the relationship, monogamy or sexual-exclusivity, and future possibilities of the present relationship. Seventy-nine percent ( N = 33) of the participants had been in their present relationship at least four years or longer.